Neotaxilanoides orientalis, a new genus and species of Tambiniini (Hemiptera: Fulgoromorpha: Tropiduchidae) from China, with a key to the world genera - Men, Qiu-Lei; Qin, Dao-Zheng (Zootaxa, 2011)
One new tropiduchid genus, Neotaxilanoides gen. n., with type species Neotaxilanoides orientalis sp. n., is described and illustrated from China. The new genus is externally similar to Neotaxilana Synave 1979, but can be distinguished from the latter by the differences in the head structure, forewing venation and male genitalia. A checklist along with a revised key to the known genera in the tribe is provided.